PROYEKSI OMSET DAN LABA MENGGUNAKAN ALGORITMA SUPPORT VECTOR MACHINE (SVM) STUDI KASUS TOKO M. ILHAM - Deni Edwar Antoni, - (2019)
This study was conducted to predict the market consumption through data obtained from resource persons. In this final project to get the desired prediction result data mining technique can be used to get turnover and profit prediction using support vector machine regression method. The data used are 340 sales data for testing using software called Matlab. Before prediction first add kernel function that is gaussian kernel, linear kernel and poly3 kernel after that pretest process normalization, number of data points, tolerance value, maximum number of iterations, mean square error and plotting. After that test 100 times for turnover and 100 times for profit with itr, maxitr and eps start from 0 - 100 to 0 - 100 to get means square error lowest after doing test it got itr and maxitr with eps 0.1 yes it 0 - 197 and 0 - 171 with mean square error of 0.0011 and 0.0011 below 1% for turnover and earnings